Preparation and characterization of Copper Chitosan Nanocomposites with Antibacterial Activity for Applications in Tissue Engineering - Maldonado Lara, K.; Luna Bárcenas, G.; Luna Hernández, E.; Padilla Vaca, F.; Hernández Sánchez, E.; Betancourt Galindo, R.; Menchaca Arredondo, J. L.; España Sánchez, B. L. (Revista Mexicana de Ingenieria Biomedica, 2017)
The present work describes the preparation of nanocomposites based on chitosan (QS)/copper nanoparticles (nCu) with antibacterial properties and potential application in tissue engineering. For this purpose, nanocomposites were prepared by solution blending with ultrasound assisted, aiming to increase the nanoparticles dispersion in the biopolymer. FTIR analyses demonstrates that nCu supported in QS increase their interaction of nanoparticles with amine/hydroxyl groups of QS molecule. UV-Vis analyses demonstrates that QS/nCu nanocomposites have an absorption signal associated with the presence of nanoparticles and the possible Cu2+ ions release in liquid media. AFM analyses shown that hydrated QS form a mesh with micro pores, improving the bacterial penetration and the direct contact with nCu. This behavior was corroborated by antibacterial assays, where QS/nCu nanocomposites shown an antibacterial activity higher than 90% between 90-180 minutes of interaction. Our results suggest that is possible to obtain combined antibacterial/biocompatible nanomaterials with potential application in tissue engineering.